THE INFLUENCE OF THE LOCK PERIOD ON THE STRESS-STRAIN STATE OF THE BEARING STRUCTURES OF ONE-STOREY BUILDINGS STEEL FRAMES (Collection of scientific works «Modern structures of metal and wood», 2019)
The  changes  in  air  temperature  cause  additional  movement  in  open  statically determinate structures, as well as in elements of closed statically indefinable structures that don’t have  a  complete  freedom  of  movement.  Mathematical  calculations  of  steel  elements  on  the temperature displacements show that displacements which occur in free rods due to the action of temperature cause noticeable changes in the geometric scheme of construction. And in the pinched rods,  stresses  arise,  the  value  of  which  reaches  one  third  of  the  steel  resistance.  That  is,  the temperature changes  in  both cases significantly affect on the stress-strain state of steel rods. The frame locking period (winter or summer) in a complete statically indefinable system can also affect the internal forces in structures and on the total stress-strain state of the building. However, there is no  study  of  the  effect  of  this  phenomenon  on  steel  frames  of  real  buildings  in  the  literature. Therefore, the aim of this work is study the effect of locking period on the internal forces in the load-bearing structures of one-story buildings steel frames. A  numerical  experiment  in  which  steel  frames  of  one-span  one-story  buildings  with dimensions of 24×108 m are simulated and calculated, in which the columns with the foundations are articulated and rigidly connected is presented. Frames were modeled in the software package Autodesk  Robot  Structural  Analysis  with  the  determination  of  internal  forces  and  stresses  in individual  structures  from  the  action  of  constant  and  variable  loads,  including  temperature differences. Based on the results of calculations for individual loads, three design combinations of efforts  were  compiled:  constant  and  variable  loads  without  taking  into  account  the  influence  of temperature; constant and variable loads, taking into account the temperature effects during summer frame  locking  period;  constant  and  variable  loads,  taking  into  account  the  temperature  effects during  winter  frame  locking  period.  For  further  analysis,  the  following  control  parameters  were selected: the greatest values of bending moments in the plane of the frame, from the plane of the frame and the greatest stresses in the group of structures. An  analysis  of  the  results  showed  that  both  with  articulated  and  rigid  fastening  in  the foundations, the cross section of the column is determined by the bending moment in the cornice of the  frame.  The cross-section of the  beam  is determined  by the reference  bending  moment  in the cornice of the frame. The moment in the middle of the span of the beam is approximately 1,5 times less than the reference moment when the columns are hinged and almost 2 times less with a rigid support of the columns. The maximum stresses from the influence of air temperature in the frame with the hinged support of the columns don’t exceed 1,3% of the stresses caused by the total effect of all loads, regardless of the locking period. This indicates an insignificant effect of temperature differences with small sizes of the frame in plan and the hinged type of support of the columns on the  foundations.  When the columns are rigidly  supported on the foundations, the air temperature affects stresses to a greater extent, increasing them to 5% during summer locking period and up to 17% during winter locking period. Therefore, the choice of the period of locking period of the steel frame, taking into account the design scheme, can serve as a means of controlling the stress-strain state of the supporting structures of the frame.